Gold, Politics and Violence: Artisanal gold mining in Kwekwe City, 1980-2022 - Nkomo, Tilda (University of the Witwatersrand, Johannesburg, 2023)
The study sought to reveal the murky, multidirectional and dynamic political, economic and socio-cultural exchanges that have often followed ‘informalisation’ of natural resource extraction in Zimbabwe. It considered how artisanal mining became a source of everyday social, political and economic contestations. In an economy that is in crisis, and a political terrain characterised by state-sponsored violence, persistent electioneering mode, politics of patronage, artisanal mining –which has directly and indirectly drawn thousands of people – has created new ideas for both the political elite and the general populace about political survival, basic economic sustenance and accumulation. It demonstrated that, for instance, politicians used artisanal mining for vote mobilisation whereas, artisanal miners needed politicians for access to the mines and related activities. As a result, the line between politicians and artisanal miners was increasingly blurred; artisanal mining was now a source of income not only to direct participants but has also benefited downstream formal and informal activities such as vending, transportation, security, among others. Building on literature that has focused on Southern Africa and other regions of the continent, the study considered how artisanal mining has contributed to both building and destroying various aspects of Zimbabwe’s wider society: the growth of new entrepreneurs, the transformation of the rural economy, the destruction of the environment, increased political and non-political violence, among other consequences. It examined everyday interactions between economic, social and political forces, with particular focus on the grassroots.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts, Department of History, School of Social Sciences, Faculty of Humanities, at the University of the Witwatersrand, Johannesburg, 2023.
Keywords: Gold; Politics; Violence; Artisanal mining; Kwekwe City; Zimbabwe; UCTD